Preparing for peace Britain's contribution and capabilities - Teuten, Richard (Whitehall paper series, 2010)
Based on some fifty interviews with civil servants across the UK government, senior military officers, politicians, academics and NGO experts, this Whitehall Paper examines the impact of reforms and initiatives over the past thirteen years, and the challenges that remain. Identifying a mismatch between ambitions and resources, the paper considers how the government can best organise itself to mitigate conflict in fragile states, with specific recommendations to ensure a robust framework for the future